The Relationship Between the Use of Android-Based Five-Tier Multiple Choice Test Diagnostic Instrument in Identifying Misconception with Students' Self-Efficacy on Chemical Equilibrium Material - Mardeni*, Putri Rizca; Anwar, Lenny; Rery, Radjawaly Usman; Linda, Roza; Nursiwan, Wimbi Apriwanda (Universitas Syiah Kuala, 2025)
Misconceptions in learning chemical equilibrium remain a persistent challenge that can hinder students' understanding and academic confidence. Despite various efforts to improve conceptual mastery, many students still harbor incorrect notions that affect their learning outcomes and self-belief. To address this issue, this study explores the relationship between students' misconceptions and their self-efficacy regarding chemical equilibrium concepts. The research employed a research and development approach using the ADDIE model, utilizing an Android-based five-tier multiple choice test as a diagnostic instrument. A random sampling technique was applied to select three senior high schools in Pekanbaru: SMAN 8 Pekanbaru, SMAN Olahraga Provinsi Riau, and SMAN 3 Pekanbaru. A correlation test was conducted to determine the presence, direction, and strength of the relationship between students' misconceptions and their self-efficacy. The results revealed a positive correlation between the two variables across schools with high, medium, and low academic profiles